Primo Levi: Science, Literature, and the Crisis of Rationality in "The Angelic Butterfly" (Ágora Journal, 2026)
This article analyzes the work of Primo Levi through the articulation between literature, science, and the crisis of rationality in the 20th century, with an emphasis on his fictional production. It proposes a methodological approach between historical and memory studies and Levi’s literary texts, expanding the horizons of historiography when faced with extreme events such as the Holocaust. The approach is based on the perspective formulated by Ivan Jablonka, which merges documentary rigor, narrative sensitivity, and ethical commitment, allowing fiction to be considered a legitimate means of constructing historical knowledge. The article is structured around three axes: 1) the historiographical tradition that frames Levi as an “exemplary” witness, contrasted with the narrative and epistemological richness of his literary work; 2) Levi’s critique of modern scientific rationality, discussed in light of Ludwig Wittgenstein’s “grammar of science”; and 3) the analysis of the short story Angelic Butterfly, from the book Natural Histories, as an example of Levi’s critique of Nazi technoscience and of scientific language as an instrument of violence. By integrating theory, literature, and history, this study proposes a renewed reading of Levi's work and its potential contributions to historical writing.
Keywords: Holocaust; Primo Levi; Historiography.